Enhanced heat tolerance in transgenic silkworm via overexpression of Pyrococcus furiosus superoxide reductase. (January 2018) - Jiang, Liang; Huang, Chunlin; Wang, Bingbing; Guo, Huizhen; Sun, Qiang; Xia, Fei; Xu, Guowen; Xia, Qingyou
Abstract: Heat shock causes a serious harm to organisms by accelerating the production of reactive oxygen species (ROS). Pyrococcus furiosus superoxide reductase (PfSOR) is an enzyme that efficiently detoxifies ROS. In order to generate a silkworm strain with high heat tolerance for sericulture, we synthesized an artificial DNA sequence encoding PfSOR based on the codon bias of Bombyx mori . PfSOR was successfully overexpressed in transgenic silkworm (named A4SOR) and BmE cells, as determined by RT-PCR and western blot analyses. An SOR activity assay confirmed that the expressed enzyme was functional in A4SOR. After exposure to a temperature of 35 °C for 44 h, the mortality rate was about 30% lower in transgenic A4SOR than in non-transgenic silkworms. Moreover, transgene expression had no apparent effect on economic characteristics of silkworms. The heat tolerance of silkworm was thus enhanced by expressing an archaeal SOR; this can be useful for sericulture in regions where the average temperature exceeds the optimal environmental temperature for B. mori of 25 °C. Graphical abstract: Highlights: DNA sequence of Pyrococcus furiosus PfSOR with Bombyx mori codon bias was expressed in silkworm. The transgenic silkworm A4SOR produced a functional PfSOR enzyme. A4SOR exhibited enhanced heat tolerance without obvious changes to economic traits.